Less abundant bacterial groups are more affected than the most abundant groups in composted tannery sludge-treated soil - Miranda, Ana Roberta Lima (Sci Rep, 2018)
The application of composted tannery sludge (CTS) has promoted shifts in soil chemical properties and, therefore, can affect the soil bacterial community. This study assessed the effect of the CTS on the soil bacterial community over time. The CTS was applied at five rates (0, 2.5, 5, 10 and 20 t/ha), and the bacterial community was evaluated for 180 days. The principal curve response (PRC) analysis showed that the most abundant phyla were not influenced by the CTS rates over time, while the analysis of the bacterial community showed that some of the less abundant phyla were influenced by the CTS rates. Similarly, the PRC analysis for the bacterial classes showed the significant effect of the CTS rates. The redundancy analyses for the bacterial phyla and classes showed the relationship between the significant chemical properties and the bacterial community of the soil after the CTS amendment over time. Therefore, there was a shift in the bacterial community over time with the application of the composted tannery sludge. Our study has shown that the less abundant bacterial groups were more influenced by the CTS than the most abundant bacterial groups and that these bacterial groups were driven by soil chemical properties, primarily chromium (Cr) and the soil pH.